1992
DOI: 10.1136/bjo.76.4.228
|View full text |Cite
|
Sign up to set email alerts
|

The course of diabetic retinopathy following cataract surgery in eyes previously treated by laser photocoagulation.

Abstract: The course of diabetic retinopathy following extracapsular cataract extraction with posterior chamber lens implantation in eyes previously treated by laser photocoagulation for diabetic retinopathy was retrospectively studied in 33 eyes (33 patients). In 20 eyes (61%) there was no change in the retinal status postoperatively. In 13 (39%) there was postoperative progression of diabetic retinopathy compared with the fellow non-operated eye, in which progression occurred in nine eyes (27%). The severity of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 13 publications
0
13
2
1
Order By: Relevance
“…We evaluated predictive factors for CME after cataract surgery performed by residents in a university-based comprehensive ophthalmology practice as well as the overall incidence of CME. It is known that cataract surgery performed by residents is associated with longer operative times and increased rates of intraoperative complications [10][11][12] ; thus, the relationship of resident-performed cataract surgery and development of CME is important for the surgical preceptor and for patient informed consent.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated predictive factors for CME after cataract surgery performed by residents in a university-based comprehensive ophthalmology practice as well as the overall incidence of CME. It is known that cataract surgery performed by residents is associated with longer operative times and increased rates of intraoperative complications [10][11][12] ; thus, the relationship of resident-performed cataract surgery and development of CME is important for the surgical preceptor and for patient informed consent.…”
Section: Resultsmentioning
confidence: 99%
“…Pollack et al 36 performed the first prospective controlled trial to evaluate the natural history of macular edema after cataract surgery. They found that only 5 of 22 patients who developed macular edema needed focal laser photocoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] In these studies, the most significant predictor for progression of DR has been the status of the DR at the time of the cataract surgery. [13][14][15][16]22,23 Similarly, diabetic macular oedema has been shown to worsen after cataract surgery, [24][25][26] although controversy remains as to the incidence of this worsening. 7,27 Some studies have shown that there are two types of worsening of macular oedema after surgery: transient pseudophakic oedema that spontaneously resolves such as Irvine-Gass syndrome [28][29][30] and actual progression of diabetic maculopathy.…”
Section: Introductionmentioning
confidence: 99%